It’s Slippery Out There’: Outsider's Perspectives of the Navigational Skills of African American Undergraduates in a Predominantly White Midwestern University - Mervin E. Chisholm; Mona Kingston (Adult Education Research Conference, 2010)
In this qualitative research study conducted at a predominantly white institution in the Midwest USA, thirteen successful African American college students were interviewed about their in-class and out-of-class experiences at the institution. The research focus was how they were experiencing college and how they were navigating the higher education terrain. The results provided evidence of an exclusionary curriculum, racial and microagressions, verbal abuse, problematic psychosocial environment and yet the defying of the odds to survive and thrive.